Tangible digital storytelling and phygital reality: benefits for inclusion and cooperation in young children - Pasqualotto Angela; Filosofi Fabio (Research on Education and Media)
Modern technology progresses at an incredibly fast pace. With personal computers, mobile phones, tablets, and the Internet, technology is used in all spheres, affecting our daily lives greatly. Educational games are also taking advantage of the technological process, for example, many useful apps are available for children. Gaming and educational opportunities have expanded because of the development of tablets and smartphones. Teachers have the opportunity to combine physical and electronic objects when creating education materials, so they are not confined to the use of traditional physical objects. Storytelling remains one of the oldest teaching methods for children: the development of technology has given impetus to the creation of tangible digital storytelling, which combines programs with physical objects, creating a single field for learning. Creating stories in which a child can interact with his/her peers has also provided new opportunities for inclusion and cooperation in young children. Indeed, the increased use of speakers, videos, pictures, and other tools that can help to quickly create and easily adapt objects for children with various backgrounds has fostered inclusive teaching. This paper will consider the evolution of the storytelling practice, focusing specifically on tangible digital storytelling and its benefits in young children.